Disaster management plan for the Immaculate Conception Academy East Library - Pascua, Rae Clement B. (2015)
Disasters are events that cause damage and destruction to humans and buildings. Libraries face emergencies such as disasters that they need to be ready for all the time. When a disaster occurs, the damages and consequences to human lives are apparent. In addition, library equipment, collections and facilities are at risk especially if the institution is not prepared.